STUDENTS' CONTRIBUTION TO ENVIRONMENTAL CONSERVATION WITH CLEANING SYSTEM CENTERED AT DARUL ULUM KUDUS ISLAMIC BOARDING SCHOOL (International Conference on Social and Islamic Studies, 2021)
This article describes the cleanliness system 'an) and waste utilization: a case study of the salaf Islamic boarding school Darul Ulum Kudus, ro'an is a term for cleaning activities in Islamic boarding schools. This research is a qualitative research that uses the type of field research or can be called field research.  This method tries to examine the status of a group of people, an object, a condition, a system of thought or a class of events in the present. From the results of the research on the cleanliness system (ro'an) in the Darul Ulum Islamic boarding school, it includes the distribution of daily schedules and ro'an, water technician channels, garbage disposal, bathroom sewerage, toilets and public kitchens of Islamic boarding schools. This Darul Ulum Kudus Islamic Boarding School accommodates about 250 male and female students. Therefore, the cleanliness of students must be considered to prevent disease in students. Including the purpose of the cleaning activity system (ro'an) of this santri to educate and instill a healthy lifestyle through the cleanliness system of the Islamic boarding school.